(untitled) (International Journal of Islamic Business, 2022)
The aim of this paper is to investigate whether trust is present between Halal fast food outlets and their Halal certified suppliers, while assessing its influence on their relationship. Online questionnaires were distributed to a sample of Halal certified fast-food outlets and restaurants in Mauritius. Descriptive and correlation analyses were then carried out. The findings show that trust does exist between the two partners concerned. At the same time, trust is seen to have a positive relationship with all the variables within the buyer-supplier relationship, namely: commitment, communication, satisfaction and long-term orientation. Also, the overall results infer that Halal food certification principles are generally being respected by Halal certified suppliers, which explains the high trust levels between them and the Halal fast food outlets they supply. Concomitantly, Halal food certification in a way contributes to better buyer-supplier relationships due to strict Halal food security and handling practices which inspire trust and confidence. The study presents a unique case in a Small Island Developing State (SID) and is one of the pioneering research on the Halal food sector in Mauritius. Despite the contribution of this research to the literature both conceptually and empirically, the small sample size, affects to some extent the generality of the findings. For this reason, more qualitative research in the form of interviews and surveys with Halal Certifying Bodies (HCBs) need to be done to acquire deeper understanding on rampant issues such as Halal frauds, Halal logo tampering and consumer trust on the Halal food certification system.